Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I need this for a proof of Wedderburn's theorem: $$q^m - 1 | q^n - 1 \quad \Rightarrow \quad m|n$$ with $q>1 \in \mathbf{N}$ and $m,n \in \mathbf{N}$.

I'd also like to know if it works the other way around: $$m|n \quad \Rightarrow \quad q^m - 1 | q^n - 1.$$


share|cite|improve this question
The other direction follows easily from the identity $(x^N - 1) = (X - 1)(X^{N - 1} + X^{N - 2} + \cdots + 1)$. – Dylan Moreland Jun 10 '12 at 19:43

Write $n=am+b$ via division algorithm: $q^m\equiv1\implies q^n-1\equiv (q^m)^aq^b-1\equiv q^b-1\bmod q^m-1$.

If this $\equiv0$ then $q^b\equiv1\Rightarrow b=0\Rightarrow m|n$. (Can't have $(q^m-1)|(q^b-1)$ otherwise; check degrees.)

For the reverse direction, apply the geometric sum formula (where $m|n$ is a given):


share|cite|improve this answer
Note this applies in the polynomial ring $\Bbb Z[x]$ rather than $\Bbb Z$. To make it applicable to an actual integer $q>1$, note that $1\le b<m$ precludes $(q^m-1)|(q^b-1)$. – anon Jun 10 '12 at 20:14

Roots of $q^n-1\in \mathbb{C}[q]$ form a group of order $n$, and the same is true for $q^m-1$.

If $q^m-1|q^n-1$ then roots of $q^m-1$ is a subgroup of roots of $q^n-1$. From Lagrange's theorem we obtain $m\;|\;n$

The inverse implication follows from the identity $$ q^{mk}-1=(q^m-1)((q^m)^{k-1}+(q^m)^{k-2}+\ldots+1) $$

share|cite|improve this answer
The argument with the roots of unity show that, as a polynomial, if $q^m-1\;|\;q^n-1$, then $m\;|\;n$. I don't see how it shows that there might not be some integer $q$ so that $q^m-1\;|\;q^n-1$ when $m\not|\;\;n$. – robjohn Jun 11 '12 at 0:32

Since $$ \frac{a^k-1}{a-1}=\sum_{j=0}^{k-1}a^j\tag{1} $$ we immediately get that $q^m-1\;|\;q^n-1$ when $m|n$.

Now, suppose that $q^m-1\;|\;q^n-1$ and that $n=km+r$ where $0\le r< m$. Then $$ \begin{align} \frac{q^n-1}{q^m-1} &=\frac{q^{km+r}-q^{km}}{q^m-1}+\frac{q^{km}-1}{q^m-1}\\ &=q^{km}\frac{q^r-1}{q^m-1}+\frac{q^{km}-1}{q^m-1}\\ &\in\mathbb{Z}\tag{2} \end{align} $$ It immediately follows from $(1)$ that $\frac{q^{km}-1}{q^m-1}\in\mathbb{Z}$. Therefore, we must also have $q^{km}\frac{q^r-1}{q^m-1}\in\mathbb{Z}$: $$ q^m-1\;|\;q^{km}(q^r-1)\tag{3} $$

Since $\left(q^{km},q^m-1\right)=1$, $(3)$ implies that $q^m-1\;|\;q^r-1$. However, since $0\le r< m$, we have that $0\le q^r-1< q^m-1$. Therefore, $q^r-1=0$; that is, $r=0$ and $n=km$; hence, $m|n$.

share|cite|improve this answer

If $m \mid n$ then write $n=mt$ and $u=q^m$. Then $q^n-1=u^t-1=(u-1)f(u)=(q^m-1)f(q^m)$, where $f(x)=1+x+\cdots+x^{t-1}$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.